Assessment of Post-Operative Cosmetic Results in Hypospadias Patients Using “HOPE” Score - Haider, Mohammad Zeeshan; Ali, Esha; Muhammad, Noor; Aslam, Mohammad (Biological and Clinical Sciences Research Journal, 2025)
Hypospadias is a common congenital anomaly of the male urethra, and surgical correction aims to achieve both functional and optimal cosmetic outcomes. The Hypospadias Objective Penile Evaluation (HOPE) score is a validated tool for assessing postoperative cosmetic appearance. However, data regarding cosmetic outcomes following staged repair techniques remain limited. Objective: To evaluate the cosmetic appearance in hypospadias patients using the Hypospadias Objective Penile Evaluation (HOPE) score. Methods: This descriptive case series was conducted in the Plastic Surgery Unit at Lady Reading Hospital from October 20, 2018, to April 20, 2019, after obtaining ethical approval. Patients diagnosed with hypospadias and scheduled for Bracka two-stage repair were included. Preoperative assessment and standardised photographs were obtained and evaluated using the HOPE score. A single surgeon performed all surgeries. Postoperative follow-up was conducted at 1 week, 3 weeks, 3 months, and 6 months. Cosmetic outcomes were assessed at 6 months postoperatively using standardised photographs. Data were collected using structured questionnaires and analysed with SPSS version 25. Mean scores were compared, and statistical significance was set at p < 0.05. Results: The mean patient age was 9.0 ± 4.52 years, with the majority of patients aged 3-10 years. The mean penile curvature and torsion were 38 ± 9.17 degrees. A distal urethral meatus was observed in 80% of cases. Mild metalar, glanular, and skin abnormalities were noted in 60% of patients. HOPE score analysis demonstrated no statistically significant difference in cosmetic outcomes across different age groups (p = 0.10). Conclusion: The cosmetic outcomes following staged hypospadias repair, as assessed by the HOPE score, were generally satisfactory and not significantly influenced by patient age. Long-term follow-up and comprehensive patient counselling are essential for optimal outcomes. Prospective studies with extended follow-up are recommended to evaluate long-term cosmetic and functional outcomes better.